ANALISIS TEKNIKAL DAN FUNDAMENTAL SAHAM PT GARUDA INDONESIA TBK: PERSPEKTIF INVESTOR INDIVIDUAL - ., LINDAWATI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
A growing number of companies are trading in its share on the stock market, then the investor is exposed to a lot of alternative investment options. The decision to invest in stocks is risky and not full certainty. The risk can never be eliminated, but only minimized. To minimized risk, an investor should carry out assassmentsof stocks, which is often done by using fundamental and technical analysis. Based on the results of the individual investor interview PT Garuda Indonesia, 5 of the 6 respondent using fundamental analysis in assessment of investment decisions on PT Garuda Indonesia. A total of three respondent who do assessment by using fundamental analysis decide to retain stock in PT Garuda Indonesia which they had purchased. Two respondents who did assessment by using fundamental analysis from aspect non financial decided to sell stock in PT Garuda Indonesia because downtrend and only one respondent who didi the assessments by using technical analysis and fundamental aspect of financial can get capital gain in doing investment on PT Garuda Indonesia. This research aims to conduct technical analysis and fundamental in PT Garuda Indonesia period February, 2011 to January 2012 to provide information as a basis for making investment decisions. The result of this research show that the stocks of PT Garuda Indonesia Tbk worth buying by investors based on technical analysis. Based on the results of fundamental analysis of stocks PT Garuda Indonesia Tbk is arguably its bad performance. So the result of technical analysis does not support the fundamental analysis results.